The impact of emotional intelligence of military leaders on the crisis management in wartime - Yevhenii Ishchenko; Iryna Yevchenko; Andrii Masliuk; Serhii Myronets; Yevhen Potapchuk (Revista Cubana de Medicina Militar)
Background: The use of effective emotion management strategies, high stress resistance, and willingness to take risks are crucial for successful crisis management in wartime. Objective: To study how the emotional intelligence of military leaders allows effective management of crisis situations during war. Methods: Emotional Questionnaire Test, Questionnaire of Psychological resilience of Servicemen of the Armed Forces of Ukraine in the Conditions of Hostilities , The Social Readjustment Rating Scale, Schubert Risk Propensity test, were applied. Descriptive analysis and regression analysis were used for statistical processing. Results: It was found that emotional intelligence determines psychological resilience (R²= 0.746, β= 1.36), stress resistance (R²= 0.721; β= 3.80), risk-taking (R²= 0.746; β= 2.29), that is, it contributes to effective crisis management. Conclusions: Emotional intelligence is a prerequisite for the development of psychological resilience, stress resistance, and risk-taking, which ensure the effectiveness of leadership decision-making in wartime. Leaders with high emotional intelligence are able to act more effectively in crisis situations.